The invasive alga Caulerpa taxifolia is not a suitable diet for the sea urchin Paracentrotus lividus - Boudouresque, C.-F.; Lemée, R.; Mari, X.; Meinesz, A. (Aquatic botany, 1996)
Food intake by the sea urchin Paracentrotus lividus (Lamarck, 1816) was investigated when sea urchins were given a diet exclusively composed of Caulerpa taxifolia (Vahl) C. Agardh, an invasive alga recently introduced into the Mediterranean. Experiments were carried out under aquarium conditions over two periods of 3 months. In the first experiment (summer/autumn), P. lividus consumed C. taxifolia 3–30 times less than control algae. In the second experiment (winter/spring), consumption of C. taxifolia by urchins was low at the beginning, but increased during the following weeks to achieve levels similar to those of controls. Whatever the period of year, urchins with C. taxifolia diet showed marked loss of spines, long righting times and small gonosomatic ratios compared with the controls. This may result either from the action of toxic substances in the alga, and/or from a too small food intake (particularly in summer).